The multifaceted presentation of chronic recurrent multifocal osteomyelitis: a series of 486 cases from the Eurofever international registry. (27th March 2018) - Girschick, Hermann; Finetti, Martina; Orlando, Francesca; Schalm, Susanne; Insalaco, Antonella; Ganser, Gerd; Nielsen, Susan; Herlin, Troels; Koné-Paut, Isabelle; Martino, Silvana; Cattalini, Marco; Anton, Jordi; et al.
Abstract: Objectives: Chronic non-bacterial osteomyelitis (CNO) or chronic recurrent multifocal osteomyelitis (CRMO) is an autoinflammatory disorder characterized by sterile bone osteolytic lesions. The aim of this study was to evaluate the demographic data and clinical, instrumental and therapeutic features at baseline in a large series of CNO/CRMO patients enrolled in the Eurofever registry. Methods: A web-based registry collected retrospective data on patients affected by CRMO/CNO. Both paediatric and adult centres were involved. Results: Complete baseline information on 486 patients was available (176 male, 310 female). The mean age of onset was 9.9 years. Adult onset (>18 years of age) was observed in 31 (6.3%) patients. The mean time from disease onset to final diagnosis was 1 year (range 0–15). MRI was performed at baseline in 426 patients (88%), revealing a mean number of 4.1 lesions. More frequent manifestations not directly related to bone involvement were myalgia (12%), mucocutaneous manifestations (5% acne, 5% palmoplantar pustulosis, 4% psoriasis, 3% papulopustular lesions, 2% urticarial rash) and gastrointestinal symptoms (8%). A total of 361 patients have been treated with NSAIDs, 112 with glucocorticoids, 61 with bisphosphonates, 58 with MTX, 47 with SSZ, 26 with anti-TNF and 4 with anakinra, with a variable response. Conclusion: This is the largest reported case series of CNO patients, showing that the range of associated clinical manifestations is rather heterogeneous. The study confirms that the disease usually presents with an early teenage onset, but it may also occur in adults, even in the absence of mucocutaneous manifestations.